Metagenomic profiling and transfer dynamics of antibiotic resistance determinants in a full-scale granular sludge wastewater treatment plant. (1st July 2022) - Calderón-Franco, David; Sarelse, Roel; Christou, Stella; Pronk, Mario; van Loosdrecht, Mark C.M.; Abeel, Thomas; Weissbrodt, David G.
Highlights: A DNA database from an AGS reactor was constructed to study the system resistome, mobilome, and microbiome. The genera Pseudomonas and Rhodoferax were the potential predominant ARG carriers in the system. MGEs and ARGs often co-localize on contigs recovered from the exDNA of the effluent. AGS plants are efficient at reducing ARB. The exDNA is an underestimated DNA fraction containing ARGs in the effluent. Abstract: In the One Health context, wastewater treatment plants (WWTPs) are central to safeguarding water resources. Nonetheless, many questions remain about their effectiveness in preventing antimicrobial resistance (AMR) dissemination. Most surveillance studies monitor the levels and removal of selected antibiotic resistance genes (ARGs) and mobile genetic elements (MGEs) in intracellular DNA (iDNA) extracted from WWTP influents and effluents. The role of extracellular free DNA (exDNA) in wastewater is mostly overlooked. This study analyzed the transfer of ARGs and MGEs in a full-scale Nereda® reactor removing nutrients with aerobic granular sludge. We tracked the composition and fate of the iDNA and exDNA pools of influent, sludge, and effluent samples. Metagenomics was used to profile the microbiome, resistome, and mobilome signatures of iDNA and exDNA extracts. Selected ARGs and MGEs were analyzed by qPCR. From 2, 840 ARGs identified, the genes arr-3 (2%), tetC (1.6%), sul1 (1.5%), oqxB (1.2%), and aph(3")-Ib (1.2%) were the most abundant among all sampling points and bioaggregates. Pseudomonas, Acinetobacter, Aeromonas, Acidovorax, Rhodoferax, and Streptomyces populations were the main potential hosts of ARGs in the sludge. In the effluent, 478 resistance determinants were detected, of which 89% were from exDNA potentially released by cell lysis during aeration in the reactor. MGEs and multiple ARGs were co-localized on the same extracellular genetic contigs. Total intracellular ARGs decreased 3-42% due to wastewater treatment. However, the ermB and sul1 genes increased by 2 and 1 log gene copies mL −1, respectively, in exDNA from influent to effluent. The exDNA fractions need to be considered in AMR surveillance, risk assessment, and mitigation strategies. Graphical abstract: Image, graphical abstract